FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA DAERAH SERTA DAMPAKNYA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN BERAU - Herlina, Elita (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
The study was intended to: 1) analyze the direct influence of Regional Income (PAD), General Allocation Fund (DAU), and the population toward Regional Expenditure. 2) Investigate the direct effects of Regional Income (PAD), General Allocation Fund (DAU) and the population to the Gross Domestic Regional Product (GDP). 3) Define the straight impact of regional expenditure to GDP in Berau. 4) Explain the indirect effects of Regional Income (PAD), the General Allocation Fund (DAU), and the population to GDP through the regional expenditure. 5) Describe the dominant effects of Regional Income (PAD), the general allocation fund (DAU) and the population to regional expenditure and GDP. The data used in this study were secondary and time series data. The result showed that Regional Income (PAD), General Allocation Fund (DAU), and total population have direct strong influence on regional expenditure and GDP. On the other hand, these factors have no significant impact to GDP through regional expenditure